Quercus Genetics Insights into the Past, Present, and Future of Oaks - Ashley, Mary; Backs, Janet R. (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The genus Quercus (Quercus, Fagaceae) comprises more than 400 species distributed throughout the northern hemisphere. While the highest oak diversity occurs in American and Asia, European species are also widespread. Oaks are ecological dominants of many temperate forests, and evergreen species are major components of Mediterranean and subtropical woodlands. They provide important ecosystem services and valuable timber. Oak species exhibit high genetic diversity, and this diversity has provided a wealth of information regarding oak ecology and evolution. Recent genetic and genomic studies of oaks have unraveled their evolutionary origins, history, and past radiations. Genetic approaches have also been applied to learn about more recent events, such as range expansions and contractions occurring at northern latitudes.